Direct endonasal approach with partial upper posterior septectomy. a “rescue flap” technique modification - Sotomayor González, Arturo; Díaz Martínez, Armando José; Radillo Gil, Ramón; García Estrada, Everardo; Morales Gómez, Jesús Alberto; Palacios Ortiz, Isaac Jair; Pérez Cárdenas, Samuel; Arteaga Treviño, Mauricio; Martínez Ponce de León, Ángel Raymundo (Georg Thieme Verlag, 2017)
Objective Report a modification of the “rescue flap” technique using a direct endonasal approach with a partial superior septectomy for approaching pituitary tumors developed in our institution. Design Prospective study. Setting Hospital Universitario “Dr. José Eleuterio González,” Universidad Autónoma de Nuevo León. Main Outcome Measures Since April 2015, we have performed 19 cases employing a direct endonasal approach with partial superior septectomy. Results and a technical note are described below. Results Nineteen patients were included in this report. Six patients presented transoperatory cerebrospinal fluid (CSF) leak, so a nasoseptal rescue flap was harvested. No patients developed postoperative CSF leak in this group. Two patients were submitted to a second surgical procedure. Nasoseptal flap was harvested without complications. In both patients, the size of the flap was enough to cover the dural defect and avoid CSF leak. Conclusion Direct endonasal approach with a partial posterior septectomy allows enough exposition of the sphenoidal sinus while preserving the nasoseptal septum with the possibility of a successful rescue flap when needed.